Analysis of the utilization of Seuseupan Weir water for irrigation in the Seuseupan Irrigation Area (Case study: Seuseupan Weir, Cirebon Regency) - Cholik, Abdul; Septyan, Ryan Benny; Winata, Hendardi; Nurdiyanto, Nurdiyanto (International Journal Labs, 2025)
The Seuseupan Dam is one of the most important water buildings in the Cirebon Regency. The purpose of this study is to analyze the need for irrigation water to obtain predictions of the maximum and minimum values of water needs, so that the availability of water can be used efficiently and effectively to increase agricultural productivity. The research contributes to understanding the effective utilization of water resources from the dam for irrigation purposes. The study provides valuable insights into water management practices, potential improvements in irrigation efficiency, and the overall impact on local agricultural productivity, as well as the financial implications of water management decisions for farmers and local economies. The findings may inform policymakers and stakeholders about the sustainability of water usage in the region, helping to optimize resource allocation and enhance food security.